Asuhan Kebidanan Berkesinambungan Pada Ny.S Dengan Penerapan Teknik Rebozo Pada Persalinan (Evidence Based Case Report) - Cecilia Favian Pramuditha; Indrayani, Diyan; Chris Sriyanti; Titi Legiati (Indonesian Health Issue, 2025)
Background: Pregnancy and childbirth are normal processes in women, pain caused during labor can cause anxiety that can inhibit contractions and disrupt the labor process, so it requires continuous care to prepare for labor since pregnancy with one of the efforts that can be done to reduce pain during labor, namely the rebozo technique which can be used to help reduce labor pain. Objective: To provide continuous care to Mrs. S by applying the rebozo technique. Method: This study uses the Evidence Based Case Report (EBCR) method. The article search was conducted on August 15, 2024 using the Pubmed, Google Scholar and Sciene Direct databases. The keywords used are words that represent the population, namely "rebozo technique" and "labor pain". The article search was limited by the inclusion criteria published in the last 5 years and full text articles so that 34 journals were obtained from 499 journals. Results: After reading all 34 journals, 3 articles were used. Then from the results of the article search, the rebozo technique was applied to reduce labor pain by measuring the pain scale using the Numeric rating scale (NRS). Before the intervention, the patient's pain scale was on a scale of 8 or severe pain. Then after the intervention, it was on mild pain. Conclusion: This continuous care is very important as an effort to prepare mothers from pregnancy to contraceptive services and this rebozo technique is recommended as one of the efforts to reduce labor pain that is prepared since pregnancy..